Cohesion in Ali Douagi’s sleepless nights and Shirley Jackson’s the lottery: A comparative study - Hamdi, Sondes (Journal of Language, Literature, Social and Cultural Studies, 2023)
Since the publication of Halliday and Hasan’s book Cohesion in English (1976), a few studies have been done on cohesion in short stories (Sari, 2016; Abed, 2016; Khaingo, 2016). However, to the best of our knowledge, not one has examined cohesion in Ali Douagi’s Sleepless Nights (1969) and Shirley Jackson’s The Lottery (1948). This paper tries to fill this gap by examining and comparing the use of grammatical cohesion and lexical cohesion in these two short stories. Using a qualitative and descriptive approach, this study identifies the grammatical and lexical cohesive devices utilized in the two short stories. The results show that both short stories utilize grammatical cohesion and lexical cohesion to build a text that “hangs together” as a consistent whole. However, a few differences between the two short stories can be observed: whereas Sleepless Nights uses the four types of grammatical cohesion (ellipsis, conjunction, reference and substitution), The Lottery is found to utilize ellipsis, conjunction and reference only. Also, a slight difference related to lexical cohesion can be observed: in The Lottery, text parts are found to be lexically tied through repetition, near-synonymy, hyponymy and antonymy. Sleepless Nights, however, utilizes hyponymy, repetition, synonymy, and antonymy. The results confirm the claim that cohesion is an integral element for any type of discourse, including short stories.